Damages limitation. (Economist, 1999)
Toshiba, which was unlucky to be the first laptop-computer maker to feel the full blast of U.S. product-liability law in the form of a class-action law suit brought by two customers in a Texan court in 1999, has also recently received a series of lessons in customer rights, most of them taught at home in Japan. In relation to its American difficulties, Toshiba decided in late October to settle out of court, rather than risk a jury ordering it to pay up to $9 billion in damages. The firm will offer rebates averaging around $330 to the 5 million customers in America who purchased Toshiba laptops in the past 12 years that contained a defective chip in the floppy-disk drive that sometimes wiped out data. In Japan, Toshiba and other manufacturers are now learning that the policy they have employed up to now—ignoring customer complaints and sometimes frightening those who complain about defective products away by threatening them with lawsuits for harassment—can cost more than listening to them. An example of how Toshiba recently learned this lesson is provided.